Adaptação de um sistema automatizado para medição de microdureza - Silva, João Moreno Vilas Boas de Souza (2006)
The hardness test is thoroughly used in research and evaluation of materials for quality control. However, this test results are subject to uncertainties caused by the process operator in the moment of the mensuration impression diagonals make by the indenter in the sample. With this mind, an automated equipment of hardness mensuration was developed. The hardness value was obtained starting from the mensuration of plastic deformation suffered by the material to a well-known load. The material deformation was calculated through the mensuration of the difference between the progress and retreat of a diamond indenter on the used sample. It was not necessary, therefore, the manual mensuration of the diagonals, decreasing the mistake source caused by the operator. Tension graphs of versus deformation could be analyzed from data obtained by the accomplished analysis, as well as you became possible a complete observation of the whole process. Following, the hardness results calculated by the experimental apparatus were compared with the results calculated by a commercial microhardness machine with the intention of testing its efficiency. All things considered, it became possible the materials hardness mensuration through an automated method, which minimized the mistakes caused by the operator and increased the analysis reliability